The efficacy of durvalumab in locally advanced lung carcinoma - Knežević, Isidora (Archive of Oncology, 2025)
Background: The integration of durvalumab, an immune checkpoint inhibitor, as consolidation therapy following platinum-based chemoradiotherapy has redefined the standard of care for patients with stage III, unresectable non-small cell lung cancer (NSCLC) who have not experienced disease progression. Although clinical trials, particularly the PACIFIC study, demonstrated significant improvements in survival outcomes, real-world data are still needed to validate these findings in routine clinical settings. This retrospective study aimed to evaluate the real-world efficacy of durvalumab in patients treated at the Institute for Pulmonary Diseases of Vojvodina, focusing on key clinical endpoints, progression-free survival (PFS), duration of clinical benefit (DoCB), and overall response rate (ORR), while exploring the influence of demographic and tumor-related factors. Methods: The study included 25 patients with stage III NSCLC, ECOG 0–1, and PDL-1 expression ≥1%, who received durvalumab after chemoradiotherapy. The treatment responses were evaluated using iRECIST criteria. The Kaplan-Meier analysis was used for survival metrics, and univariate Cox regression assessed the impact of histology, smoking status, PDL-1 expression, gender, and ECOG status. Results: A partial response was achieved in 36% of the patients, stable disease in 40%, and progression in 24%, with an ORR of 36%. The mean PFS was 19.8 months, and DoCB 25 months. Although the adenocarcinoma subtype, female gender, lower pack-year index, and higher PDL-1 expression suggested more favorable outcomes, no statistically significant differences were found. Conclusion: These findings confirm the clinical benefit of durvalumab consolidation in real-world practice, with outcomes comparable to pivotal trials. Despite the small sample size, the observed trends highlight potentially relevant prognostic markers. Expanding the patient cohort and extending the follow-up will further clarify these associations and support the evidence-based personalization of the NSCLC treatment.